Postmenopausal Osteoporosis: The Role of Immune System Cells. (23rd May 2013) - Faienza, Maria Felicia; Ventura, Annamaria; Marzano, Flaviana; Cavallo, Luciano
Abstract : In the last years, new evidences of the relationship between immune system and bone have been accumulated both in animal models and in humans affected by bone disease, such as rheumatoid arthritis, bone metastasis, periodontitis, and osteoporosis. Osteoporosis is characterized by low bone mass and microarchitectural deterioration of bone tissue with a subsequent increase in bone fragility and susceptibility to fractures. The combined effects of estrogen deprivation and raising of FSH production occurring in menopause cause a marked stimulation of bone resorption and a rapid bone loss which is central for the onset of postmenopausal osteoporosis. This review focuses on the role of immune system in postmenopausal osteoporosis and on therapeutic strategies targeting osteoimmunology pathways.